Impact of rainfall regime on chemical composition, digestibility, and methane production of Echinochloa polystachya (Kunth) Hitch - Díaz-Céspedes, Medardo (2020)
The aim in this study was to determine the chemical composition, digestibility, and methane production of Echinochloa polystachya (Kunth) Hitch in periods with different rainfall in the Peruvian rainforest region. The pasture was managed under a rotational grazing system. The nutritive quality and in vitro CH4 production of the pasture during both experimental periods was determined from a sample obtained by zigzag technique and sampling points using the method of destructive systematic sampling. Echinochloa polystachya in the period of lower than higher rainfall had a higher content of neutral detergent fiber (NDF) (p < 0.001) and acid detergent fiber (ADF) (p < 0.001). Organic material (OM) was higher in the period of greater rainfall (p < 0.001); however, the crude protein (PC) content (p = 0.11), in vitro digestibility of OM (p = 0.89), corrected net gas production (p = 0.83) and in vitro CH4 output (p = 0.63) were similar for rainfall periods.